3D TCAD Simulation for Semiconductor Processes, Devices and Optoelectronics - Li, Simon; Li, Suihua (Springer New York : Imprint: Springer, 2012)
Technology computer-aided design, or TCAD, is critical to today's semiconductor technology and anybody working in this industry needs to know something about TCAD.  This book is about how to use computer software to manufacture and test virtually semiconductor devices in 3D.  It brings to life the topic of semiconductor device physics, with a hands-on, tutorial approach that de-emphasizes abstract physics and equations and emphasizes real practice and extensive illustrations.  Coverage includes a comprehensive library of devices, representing the state of the art technology, such as SuperJunction LDMOS, GaN LED devices, etc. Provides a vivid, internal view of semiconductor devices, through 3D TCAD simulation; Includes comprehensive coverage of  TCAD simulations for both optic and electronic devices, from nano-scale to high-voltage high-power devices; Presents material in a hands-on, tutorial fashion so that industry practitioners will find maximum utility; Includes a comprehensive library of devices, representing the state of the art technology, such as SuperJunction LDMOS, GaN LED devices, etc.    .